Efficient Amino‐Sulfhydryl Stapling on Peptides and Proteins Using Bifunctional NHS‐Activated Acrylamides. (1st April 2021) - Silva, Maria J. S. A.; Faustino, Hélio; Coelho, Jaime A. S.; Pinto, Maria V.; Fernandes, Adelaide; Compañón, Ismael; Corzana, Francisco; Gasser, Gilles; Gois, Pedro M. P.
Abstract: Widely used reagents in the peptide functionalization toolbox, Michael acceptors and N ‐hydroxysuccinimide (NHS) activated esters, are combined in NHS‐activated acrylamides for efficient chemoselective amino‐sulfhydryl stapling on native peptides and proteins. NHS‐activated acrylamides allow for a fast functionalization of N ‐terminal cysteines ( k 2 =1.54±0.18×10 3  M −1  s −1 ) under dilute aqueous conditions, enabling selectivity over other nucleophilic amino acids. Additionally, the versatility of these new bioconjugation handles was demonstrated in the cross‐linking of in‐chain or C ‐terminal cysteines with nearby lysine residues. NHS‐activated acrylamides are compatible with the use of other cysteine selective reagents, allowing for orthogonal dual‐modifications. This strategy was successfully applied to the late‐stage functionalization of peptides and proteins with a PEG unit, fluorescent probe, and cytotoxic agent. The level of molecular control offered by NHS‐activated acrylamides is expected to promote amino‐sulfhydryl stapling technology as a powerful strategy to design functional bioconjugates. Abstract : Michael acceptors and N ‐hydroxysuccinimide activated esters stand among the most used reagents in the peptide functionalization toolbox. These two types of functional groups are merged in NHS‐activated acrylamide reagents for efficient chemoselective amino‐sulfhydryl stapling on native peptides and proteins. This is a versatile strategy for orthogonal dual‐modification and late‐stage design of functional bioconjugates.